Management of business projects of the enterprise as a factor of increasing international competitiveness in the conditions of global sustainability - Zybareva, Oksana V.; Shylepnytskyi, Pavlo; Krylov, D.; Arefiev, S; Ozarko, Kateryna; Hryhorkiv, Mariia (My University, 2022)
The article is devoted to the substantiation of the conceptual aspects of business project management, which is caused by the aggravation of international competition in the context of the establishment of sustainable development. The purpose of the study is to substantiate theoretical and methodological principles of the business projects management of enterprises, which will contribute to increasing international competitiveness in the conditions of global sustainability. The research used resource and system approaches, as well as the principles of purposefulness, interaction and efficiency of business project management. The functional dependence of the business project management is substantiated. Directions for improving the business projects management in the area of critical deviations of the trajectory of the project state are proposed. It has been proven that the randomness and uncontrollability of events form the variability of the expected value of the result of the business project management and expands the range of searching for the goals achievement with the deviation minimization of the project execution trajectory from the planned one. It has been justified that taking into account and increasing managerial methodological, financial, production, scientific and innovative and marketing potentials contributes to increasing the competitiveness of enterprises in the international market in the conditions of global sustainability.
Keywords: business project, enterprise, international competitiveness, global sustainability, project management